Review Impact of the Spatial Development Patterns on Water Ecology of Cisadane Watershed - Ujang Sudiartono; Abdul Razak; Eni Kamal; Isril Berd (Science and Environmental Journal for Postgraduate, 2022)
A Watershed is a land area that is an ecosystem unit with rivers and their tributaries that function to accommodate, store, and drain water that comes from rainfall to lakes or seas naturally, whose boundaries on land are topographical and separator boundary in the sea up to the watering area which is still affected by land activities. Characteristics and ecological conditions of the watershed environment are influenced by changes in spatial use patterns with reduced land cover in the watershed area will affect watershed conditions. Human intervention with various activities, especially economic, industrial and residential activities in the upstream to downstream watershed areas affects the water cycle (hydrological cycle) as well as the quality and quantity of the aquatic ecology of the watershed environment. Efforts to maintain the availability of green open space in the watershed area is one of the important things to be able to maintain and maintain water ecology in the Cisadane watershed in addition to various efforts to maintain the water quality of the watershed so that various unique aquatic biota can still be maintained and well maintained. The involvement of local governments, stakeholders, and the community is one of the most important things in preserving and maintaining the environmental conditions of watersheds.